High velocity impact, flexural and dynamic mechanical properties of flax/carbon/Kevlar reinforced bio-phenolic/epoxy composites - Ismail, Ahmad Safwan; Mohammad, Jawaid; Ramlee, Nor Azlina; Abu-Jdayil, Basim (Elsevier Editora Ltda, 2024)
This work investigated the effect of hybridization of flax fabric (FF) with carbon/Kevlar fabric (CK) on the flexural, dynamic mechanical analysis and high velocity impact. Hand lay-up technique was used to fabricated different ratio of flax to carbon/Kevlar hybrid composites, which were hot-pressed and then cured. It was revealed that increase in ratio of CK has improved the flexural properties, storage modulus, loss modulus, energy absorption and ballistic limit of the composites. Interestingly, hybrid composite with ratio 25:75(FF:CK) has highest flexural properties, storage modulus and loss modulus among the other composites. The cole-cole plot and damping factor reveals that hybrid composite with ratio 25:75(FF:CK) has the strongest fibre/matrix adhesion. The hybrid composite with ratio 25:75 (FF:CK) displayed the highest Tg. Based on high velocity impact test, it was shown that there is not much different in energy absorption and ballistic of the hybrid composites compared to plain CK composite. FF/CK hybrid composites have the potential to be used in high performance application such as ballistic helmet.